Guarantee of Legal Protection for Child Laborers Regarding Types of Work and Working Hours in Accordance with Normative Rules - Aini Suniaprily, Firstnandiar Glica; Ardhani Putri, Hanuring Ayu; Dewi, Nourma (IHSA Institute, 2024)
The problem now is, whether child labor is actually allowed in accordance with Law Number 35 of 2014 concerning Child Protection or based on Law Number 6 of 2023 concerning Employment Cluster Job Creation or whether there are exceptions to the arrangements for child labor It is necessary to pay attention to how the state pays attention to the problem of child labor, then we must also be observant of the factors that cause the rampant phenomenon of child labor in Indonesia.The type of research used is normative juridical legal research, said to be normative legal research because it uses primary data sourced from library data and laws and regulations. This research uses a statutory approach, namely an approach to examine the laws and regulations related to the protection of child labor. In addition to using a statutory approach, a literature approach is also used to collect secondary legal materials.Special laws to protect children's rights in Indonesia are contained in Law Number 35 of 2014 concerning Child Protection. The Law on Child Protection is a concrete form of affirmation of the legalization of children's rights derived from the Convention on the Rights of the Child and national legal norms. Based on Law Number 35 of 2014 concerning Child Protection and Law Number 13 of 2003 which has changed to Law Number 6 of 2023 concerning Employment Cluster Job Creation, it explains that children are actually allowed to work as long as they are in accordance with the criteria stated in the laws and regulations, more precisely regarding the rules for the type of work and appropriate working hours, and when a child works, they must meet the conditions that have been described as well